(untitled) (Asean Journal of Engineering Education, 2025)
This study presents the development and validation of a survey instrument designed to assess the competence of biomedical engineers in AI-integrated healthcare settings. Based on the KSAA (Knowledge, Skills, Abilities, and Attitudes) framework, the instrument incorporates AI readiness and perceived organisational support (POS) as mediators of job performance. The items were adopted and adapted from established studies and refined through expert opinion analysis involving five experts from academia and industry, followed by feedback from 10 postgraduate reviewers. A pilot study was conducted with 40 biomedical engineers in this study group using the same criteria as the intended full-scale study. Data were analysed using SPSS version 30.0, focusing on internal consistency through reliability analysis. Results showed strong reliability across all dimensions, with Cronbach’s alpha values ​​ranging from 0.823 to 0.897. This paper only reports the validation phase of the instrument; testing of the mediation hypothesis will be conducted in a subsequent full-scale study. Validated instruments provide a reliable foundation for future workforce development, training programmes, curriculum enhancements, and large-scale data collection in AI-driven healthcare environments.